Resolution of lateral acoustic space assessed by electroencephalography and psychoacoustics - Bennemann, Jan; Freigang, Claudia; Schröger, Erich; Rübsamen, Rudolf; Richter, Nicole (Frontiers in Psychology, 2013)
The encoding of auditory spatial acuity (measured as the precision to distinguish between two spatially distinct stimuli) by neural circuits in both auditory cortices is a matter of ongoing research. Here, the event-related potential mismatch negativity (MMN), a sensitive indicator of preattentive auditory change detection, was used to tap into the underlying mechanism of cortical representation of auditory spatial information. We characterized the MMN response affected by the degree of spatial deviance in lateral acoustic space using a passive oddball paradigm. Two stimulation conditions specifically focusing on the investigation of the mid- and far-lateral acoustic spcace were considered: (i) 65° left standard position with deviant positions at 70°, 75°, and 80°; and (ii) 95° left standard position with deviant positions at 90°, 85°, and 80°. Additonally, behavioral data on the minimum audible angle (MAA) were acquired for the respective standard positions (65°, 95° left) to quantify spatial discrimination in separating disctinct sound sources. The two measurements disclosed the linkage between the (preattentive) MMN response and the (attentive) behavioral threshold. At 65° spatial deviations as small as 5° reliably elicited MMNs. Thereby, the MMN amplitudes monotonously increased as a function of spatial deviation. At 95°, spatial deviations of 15° were necessary to elicit a valid MMN. The behavioral data, however, yielded no difference in mean MAA thresholds for position 65° and 95°. The different effects of laterality on MMN responses and MAA thresholds suggest a role of spatial selective attention mechanisms particulary relevant in active discrimination of neighbouring sound sources, especially in the lateral acoustic space.